(x/4)-(x+2/3)+(1/6)=0

Simple and best practice solution for (x/4)-(x+2/3)+(1/6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x/4)-(x+2/3)+(1/6)=0 equation:


x in (-oo:+oo)

x/4-x-(2/3)+1/6 = 0

x/4-x-2/3+1/6 = 0

-3/4*x-1/2 = 0 // + 1/2

-3/4*x = 1/2 // : -3/4

x = 1/2/(-3/4)

x = -2/3

x = -2/3

See similar equations:

| 3.2x-11.9+0.8x+6= | | x/4-x+2/3+1/6=0 | | 3y-12=17 | | 6(x+5)-(x-4)=7x-6 | | 6.8x-2=5.8x | | 6/4y=4 | | 6/4y-4 | | 2(3x+5)=2x-2 | | .50x+.45(70)=37.5 | | 14/3=34/3-4/3(10r-2) | | 12-3(4-t)+4t= | | -(8/2p-2)+5/2p+2=-9/4p^2-4 | | 3x+17y=23 | | 23-2(17+27)= | | 3x+17y=17 | | 3ab+2ab+9ab= | | -6x^2+x+35=0 | | -4p+(5p-5)/2=7/4 | | 5+1x=60 | | 6x^2+x+35=0 | | 4x^4-12x^2=-9 | | 4/x-3=-6/x+5+12/(x-3)(x+5) | | 8=-9b+8 | | 5x-6+2x=x+5 | | 17=7z-9z+5 | | x=y-z/5 | | -6t^2+4t+5=0 | | 4(m-2)+3m= | | 4K-2/3+5/3(3K+4) | | 3.5y-3.4=7.1 | | 343x^6+729x^3= | | -9u+9=0 |

Equations solver categories